Identification of Risk Factors for The Implementation Stage of Toll Road Construction in Public-private Cooperation Using the BOT (Build Operate Transfer) System - Akhirini Akhirini; Zuul Fitriana Umari (Universitas Medan Area, 2023)
One type of infrastructure that falls under the jurisdiction of the government is toll roads. Government restrictions provide investors with opportunities to collaborate in the construction of toll road infrastructure, one of which is the BOT (Build Operate Transfer) system. For investors, there are numerous risks associated with the deployment of toll roads with the BOT system. With research limitations at the construction implementation stage, the goal of this study is to pinpoint variables that could end up becoming hazards for investors during the toll road development process. In this study, observation, interviews, and questionnaires for the targeted target respondents were the methods employed. Quantitative statistical analysis is used in data analysis to create categories in the shape of quadrants. The research's findings identified 17 risk factors that are broken down into three risk sub-categories. According to the results of the quadrant charting, 1 variable (inflation factor) was at moderate risk, 2 factors (field conditions and predicted construction costs) were deemed to be high risk, 7 variables were at substantial risk, and 7 variables were low risk.